Band Structure Engineering of WSe2 Homo‐Junction Interfaces via Thickness Control (Adv. Mater. Interfaces 4/2022). Issue 4 (3rd February 2022) - Shin, June‐Chul; Kim, Yeon Ho; Watanabe, Kenji; Taniguchi, Takashi; Lee, Chul‐Ho; Lee, Gwan‐Hyoung
Abstract : Band Structure Engineering of WSe2 Homo‐Junction Interfaces In article number 2101763, June‐Chul Shin, Gwan‐Hyoung Lee, and co‐workers demonstrate that vertical homo‐junction consisting of two WSe2 flakes with different thicknesses shows anti‐ambipolar transport behavior due to a thickness‐induced band offset at the interface. The anti‐ambipolar transport is due to tunneling‐mediated interlayer recombination of the majority carriers of electrons in few‐layer WSe2 and holes in monolayer WSe2 .